Influence of adjacent teeth on the accuracy of intraoral scanning systems for class II inlay preparation. Issue 5 (5th October 2021) - Kim, Jae‐Hoon; Son, Sung‐Ae; Lee, Hyeonjong; Yoo, Yeon‐Jee; Hong, Seoung‐Jin; Park, Jeong‐Kil
Abstract: Objective: This study aimed to evaluate the influence of the presence of adjacent teeth on the accuracy of intraoral scanning (IOS) systems for class II inlay preparation. Materials and Methods: The mesio‐occlusal inlay preparation was prepared in an anatomical model of the maxillary molar. The prepared tooth was secured to a typodont with the mesial adjacent tooth removed or in situ. Ten digital impressions of the inlay preparation were acquired using three IOS systems (CEREC Primescan, 3Shape TRIOS 3, and Medit i500). A laboratory scanner (3Shape E3) was used to obtain the reference scan data. The mean absolute deviation values were calculated to evaluate the accuracy of the digital models. Results: The group with the adjacent teeth present showed lower trueness and precision compared to that without the adjacent tooth ( p <  .05). Significant differences were observed among the IOS systems ( p <  .05). Primescan showed the highest accuracy, irrespective of the presence of adjacent teeth. Conclusions: The presence of the adjacent tooth negatively affected the accuracy of all the IOSs tested. Although the performance of Primescan was superior to that of TRIOS 3 and i500, each IOS system showed clinically acceptable levels of accuracy for class II inlay preparation. Clinical Significance: The adjacent tooth can be a confounding factor for accurate digital impressions of class II inlay preparation.